Validation of an analytical method using HPLC–MS/MS to quantify osimertinib in human plasma and supplementary stability results. (3rd February 2020) - van Veelen, Ard; van Geel, Robin; de Beer, Yvo; Dingemans, Anne‐Marie; Stolk, Leo; ter Heine, Rob; de Vries, Frank; Croes, Sander
Abstract: A new method for quantification of osimertinib (OSIM) in human plasma using a high‐performance liquid chromatography–tandem mass spectrometry method was developed and validated. Methanol was used for protein precipitation and pazopanib as internal standard. Separation was performed on a HyPURITY®C18 analytical column (50 × 2.1 mm; 3 μm) using a gradient elution of ammonium acetate in water and ammonium acetate in methanol, both acidified with formic acid 0.1%. Detection and quantification of OSIM and pazopanib was performed using a triple quadruple mass spectrometer after electrospray ionization. This method led to robust results, as the selectivity, carryover, precision and accuracy all met pre‐specified requirements. OSIM was stable in human serum when stored at −80°C. Reduced stability was found when stored at 2–4°C or room temperature. Degradation of OSIM slowed down in EDTA–plasma and acidified human serum. The limited stability of OSIM at room temperature should be considered for transport and sample preparation. Plasma samples should be frozen as soon as possible and sample preparation should be performed on dry‐ice. In the future, EDTA–plasma and sample acidification may be used to improve OSIM stability at room temperature. However, more research and validation of such an approach are required.